Exogenous and endogenous hyaluronic acid reduces HIV infection of CD4+ T cells. Issue 9 (24th June 2014) - Li, Peilin; Fujimoto, Katsuya; Bourguingnon, Lilly; Yukl, Steven; Deeks, Steven; Wong, Joseph K
Abstract : Preventing mucosal transmission of HIV is critical to halting the HIV epidemic. Novel approaches to preventing mucosal transmission are needed. Hyaluronic acid (HA) is a major extracellular component of mucosa and the primary ligand for the cell surface receptor CD44. CD44 enhances HIV infection of CD4 + T cells, but the role of HA in this process is not clear. To study this, virions were generated with CD44 (HIVCD44 ) or without CD44 (HIVmock ). Exogenous HA reduced HIV infection of unstimulated CD4 + T cells in a CD44‐dependent manner. Conversely, hyaluronidase‐mediated reduction of endogenous HA on the cell surface enhanced HIV binding to and infection of unstimulated CD4 + T cells. Exogenous HA treatment reduced activation of protein kinase C alpha via CD44 on CD4 + T cells during infection with HIVCD44 . These results reveal new roles for HA during the interaction of HIV with CD4 + T cells that may be relevant to mucosal HIV transmission and could be exploitable as a future strategy to prevent HIV infection.